Combined Effects of Fishing and Environment on the Growth of Larimichthys polyactis in Coastal Regions of China - Zhuo Yin; Yun Xia; Chi Zhang; Rui Zhang; Dan Liu; Yang Liu (Fishes)
In fisheries’ stock assessments, the concept of “growth plasticity”—the ability of organisms to modulate their growth rates in response to environmental conditions—has gained attention in recent years. Historically, the impacts of fishing activities and environmental fluctuations were considered separately, while their combined effects have recently come into focus. This study collected 834 adult small yellow croakers (Larimichthys polyactis) from the northern Yellow Sea, the central Yellow Sea, the southern Yellow Sea, and the northern East Sea by trawling during 2020–2021. Using otolith increments as a proxy for annual somatic growth, the study reconstructed otolith chronologies during 2015–2020 for these four stocks. The results of the mixed-effects modeling suggested that temperature during spawning and previous overwintering seasons had comparable importance for the annual growth of small yellow croakers, with higher temperature promoting growth. The growth of small yellow croakers was also found to be correlated with ENSO events, with a lag of 1 to 2 years. A further investigation into combined effects revealed that higher fishing pressure might inhibit the small yellow croaker’s response to favorable environmental conditions. Furthermore, considering the potential differences in growth plasticity among stocks, an analysis was conducted on the spatial variations in growth response to these factors. The analysis revealed that, compared to the stocks in the Yellow Sea, the stock from the East China Sea could exhibit higher growth, superior adaptability to temperature, and a distinctive response to fishing pressure. In conclusion, the present study, while primarily focusing on temperature, preliminarily analyzed the combined effects of fishing and environment and underscored the differences in growth plasticity between stocks in the Yellow Sea and the East China Sea. Despite the limited factors analyzed in this study, it suggests a direction for future studies, highlighting the necessity to include more environmental factors, and even population factors (e.g., the biomass of preys), for a more comprehensive understanding of the combined effects. Based on the observed differences between the two potential subpopulations, this study also provides new insights for the management of the small yellow croaker based on metapopulation dynamics.